Development of a cultural heritage object BIM model - Braila, Natalya; Vakhrusheva, Svetlana; Martynenko, Elena; Kisel, Tatyana (IOP conference series. Earth and environmental science, 2017)
The BIM technology during her creation has been aimed, first of all, at design and construction branch, but its application in the field of studying and operation of architectural heritage can essentially change and transfer this kind of activity to new qualitative level. The question of effective introduction of BIM technologies at the solution of administrative questions of operation and development of monuments of architecture is considered in article. Creation of the information model of the building object of cultural heritage including a full complex of information on an object is offered: historical and archival, legal, technical, administrative, etc. The 3D model of an object of cultural heritage with color marking of elements on degree of wear and a first priority of carrying out repair will become one of components of model. This model will allow to estimate visually technical condition of the building in general and to gain general idea about scales of necessary repair and construction actions that promotes improvement of quality of operation of an object, and also simplifies and accelerates processing of information and in need of a memorial building assessment as subject to investment.